Pengaruh Pemanfaatan Sistem Informasi Akuntansi dan Penggunaan Teknologi Informasi terhadap Kinerja UMKM Sektor Pengolahan Makanan dan Minuman - Isma Wahyuni Ismail, Sri; Samsinar, Samsinar; Oktaviyah, Nurafni (Green Publisher Indonesia, 2025)
In the digital era, the adoption of technology and information systems is crucial to improve business performance, including in the MSME sector. This study analyzes the influence of the use of accounting information systems (SIA) and the use of information technology (IT) on the performance of MSMEs in the food and beverage processing sector. MSME (Y) performance is measured from financial statements, sales levels, targets, and profit growth. The utilization of SIA (X1) is assessed through financial planning, cash and inventory recording, quality of financial statements, decision-making, and internal controls, while IT usage (X2) is measured through hardware, software, databases, social media, and usage intensity. This study surveyed 92 MSMEs in Pallangga District using random sampling techniques. Data collection uses questionnaires and interviews, which are analyzed by multiple linear regression. The results showed that SIA and IT utilization significantly affected the performance of MSMEs (F = 59.535, p < 0.05). Partially, the use of SIA has a positive effect on the performance of MSMEs (p = 0.001), as well as the use of IT (p = 0.002). These findings highlight the role of digitalization and information systems in increasing the competitiveness and growth of MSMEs in the modern era.